2006
DOI: 10.2527/2006.8461422x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementation of β-glucans on growth performance, nutrient digestibility, and immunity in weanling pigs

Abstract: Two experiments were conducted to evaluate the efficacy of beta-glucan on growth performance, nutrient digestibility, and immunity in weanling pigs. In Exp. 1, 210 weanling pigs (6.38 +/- 0.92 kg of BW) were fed dietary beta-glucan (0, 0.01, 0.02, 0.03, or 0.04%) for 5 wk. In Exp. 2, 168 pigs (6.18 +/- 1.31 kg of BW) were fed no beta-glucan or antibiotics (T1), 0.02% beta-glucan (T2), only antibiotics (T3), or 0.02% beta-glucan with antibiotics (T4) for 8 wk. In Exp. 2, the antibiotics fed were apramycin and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
2
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(78 citation statements)
references
References 10 publications
7
64
2
4
Order By: Relevance
“…Their bond to specifi c receptors stimulates the activity of phagocytes and triggers signal cascades leading to expression of cytokines and chemokine genes, which was confi rmed in piglets in several in vivo and in vitro studies [18,22,23]. Besides reported higher weight gain, there are also reports of their stimulating effect on increased resistance of suckling piglets against infectious agents, their infl uence on phagocytic activity of cells and production of reactive forms of oxygen, proliferative activity of lymphocytes, and expression of specifi c receptors [24,25]. With this aim, we performed the experiment on weaned piglets, where after immune-modulation of sows and expectation of higher trans-colostral transfer of immunoglobulins, a higher production of specifi c antibodies after oral vaccination of weaned piglets was expected.…”
Section: Discussionmentioning
confidence: 97%
“…Their bond to specifi c receptors stimulates the activity of phagocytes and triggers signal cascades leading to expression of cytokines and chemokine genes, which was confi rmed in piglets in several in vivo and in vitro studies [18,22,23]. Besides reported higher weight gain, there are also reports of their stimulating effect on increased resistance of suckling piglets against infectious agents, their infl uence on phagocytic activity of cells and production of reactive forms of oxygen, proliferative activity of lymphocytes, and expression of specifi c receptors [24,25]. With this aim, we performed the experiment on weaned piglets, where after immune-modulation of sows and expectation of higher trans-colostral transfer of immunoglobulins, a higher production of specifi c antibodies after oral vaccination of weaned piglets was expected.…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that β-glucans possess anti-inflammatory properties enhancing anti-inflammatory cytokine production in pigs (Li et al 2006). In some situations, glucans may stimulate growth and feed intake but also depress piglet's performance (Hahn et al 2006).…”
Section: Prebioticsmentioning
confidence: 99%
“…Whereas the ability of lymphocytes to proliferate is also insensitive to a feed supplementation with glucans (Hiss and Sauerwein, 2003), the production of the different classes of Igs is influenced in a dose-dependent manner with lower and higher doses favouring IgA and IgG responses, respectively (Sauerwein et al, 2007). This could be partly correlated to the different pattern of lymphocyte subclasses (helper and cytotoxic T-cells) observed in response to a supplementation with b-glucans (Hahn et al, 2006). However, those variations are inconstantly reported, and appear to be related to the period of supplementation Hahn et al, 2006).…”
Section: Natural Alternatives To In-feed Antibioticsmentioning
confidence: 99%
“…This could be partly correlated to the different pattern of lymphocyte subclasses (helper and cytotoxic T-cells) observed in response to a supplementation with b-glucans (Hahn et al, 2006). However, those variations are inconstantly reported, and appear to be related to the period of supplementation Hahn et al, 2006). The effect of dietary supplementation with b-glucans on the response to systemic immunisation has produced contrasting results.…”
Section: Natural Alternatives To In-feed Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation